IMPACT OF VITAMIN E AND SELENIUM TREATMENT IN-OVO AND AFTER HATCHING OF BROILER - Abdul-Majeed, A. F.; Abdul-Rahman, S. Y. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the effect of in-ovo injection with vitamin E and selenium during the incubation and post-hatching period. 360 fertilized eggs of Ross 308 broiler breeders were incubated, then distributed on 10th day into three groups (120 eggs/group). 1st group: uninjected eggs, 2nd group: eggs were injected with 0.1 ml deionized water/egg in the chorioallantoic cavity, and 3rd group: eggs were injected with 0.1 ml/egg of Introvit-E-Selen in chorioallantoic cavity. After hatching, 270 chicks were randomly distributed into six groups, and reared until 42 days aged as follows: birds in 1st, 3rd and 5th groups drinks tap water only (free from any addition), while birds of other groups, were reared on drinking water supplemented with 12.5 mg vitamin E and 500 µg sodium selenite/liter water. Results showed a significant increase in hemoglobin, lymphocytes% and serum globulin, and a significant decrease in packed cell volume%, heterophils%, heterophils/lymphocytes ratio, glucose, cholesterol, triglycerides and albumin concentration as compared with control. In conclusion, vitamin E and selenium have enhanced some immunological aspects and reduced stress, as well as a number of hematological parameters of broiler chicks, also, the continuity of Vit.E-Selenium addition led to continuous improvement of physiological parameters, and when it stopped, the values of those parameters were retracted.